City Bus Tour Evaluation in Indonesia: Study Case of Jogja Heritage Track - Azzahrah, Fatimah (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2023)
Along with the development of tourism in Yogyakarta, governments have created programs that support regional tourism icons, one of which is by creating city bus tours. Kundha Kabudayan DIY is one of them, in order to introduce the history and culture of Yogyakarta, Jogja Heritage Track bus tour program was created. The uniqueness of the bus tour program is that the vehicle’s value as an attraction is more dominant than the utility value as a transportation. This research examines the travel bus experiences of tourists who have taken the Jogja Heritage Track bus tour. The theory from Carriera et al (2014) regarding the travel bus experience with seven variables, namely staff’s skills, information provision, social environment, vehicle maintenance, ticket line service, off-board facilities and individual space will be adapted to the Jogja Heritage Track program. Using a questionnaire as a research instrument distributed to 100 Jogja Heritage Track tourists. The results of the quantitative descriptive analysis indicate that tourists have experienced the